2022
DOI: 10.3390/polym14071306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Squid Cartilage Chitosan Molecular Structure on the Properties of Its Monofilament as an Absorbable Surgical Suture

Abstract: Suture is an important part of surgery, and wounds closing after surgery remains a challenge for postoperative care. Currently, silk, linen fiber, and cotton are available in the market as non-absorbable suture biomaterials. So, there is an urgent need to develop a novel suture with advantageous characteristics compared to the ones available on the market. In present study, a series of ultra-high molecular weight chitosan with different DD and MV were prepared from squid cartilage by alkaline treatment and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Chitosan scaffolds have a porous structure, enabling the enzyme to be transported to the structure of the material as well as allowing any degradation products to diffuse from the structure . The degradation of wet-spun chitosan fibers showed that chitosan with a higher degree of deacetylation had a lower degradation speed, and the lowest residual ratio achieved after 5 weeks was around 85% . Wet-spun chitin fibers, on the other hand, were reported to have a higher degradation rate, reaching down to 53% residual mass after 15 days in a lysozyme/PBS solution …”
Section: Resultsmentioning
confidence: 99%
“…Chitosan scaffolds have a porous structure, enabling the enzyme to be transported to the structure of the material as well as allowing any degradation products to diffuse from the structure . The degradation of wet-spun chitosan fibers showed that chitosan with a higher degree of deacetylation had a lower degradation speed, and the lowest residual ratio achieved after 5 weeks was around 85% . Wet-spun chitin fibers, on the other hand, were reported to have a higher degradation rate, reaching down to 53% residual mass after 15 days in a lysozyme/PBS solution …”
Section: Resultsmentioning
confidence: 99%
“…To begin with, chitosan has been used for the development of different drug delivery systems, including mucoadhesive, multiparticulate parenteral, and floating oral drug delivery systems [26][27][28][29][30]. Moreover, chitosan has been explored for tissue engineering, sutures, and wound dressings, taking advantage of its bacteriostatic and healing properties [31][32][33][34]. Other applications include the development of biosensors [35].…”
Section: Chitosan-based Materials and Devicesmentioning
confidence: 99%
“…These devices can be made up of a monofilament or a set of twisted or braided filaments. There are some requirements for sutures, including good mechanical properties and high biocompatibility [34,160]. Among the most frequent problems attributable to the sutures used today, the frequent infection of the tissues adjacent to the sutured wounds has recently attracted the attention of researchers.…”
Section: Suturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan (CS), as a promising biopolymer, has the advantages of low cost, nontoxicity, biocompatibility, and biodegradability. CS fibers have shown broad biomedical clinical applications such as surgical sutures, [1] wound dressing, [2,3] artificial skin, [4] and 3D scaffolds for tissue engineering. [5,6] The excellent antibacterial activity and spinnability make CS very suitable for fabrics in the textile field, especially for underwear and home textiles.…”
Section: Introductionmentioning
confidence: 99%